Aircraft Maintenance Technician Perceptions and Evaluations about the Safety Culture and Responsibility Related Competencies - Tarık Güneş; Uğur Turhan; Birsen Açıkel (Journal of Aerospace Technology and Management)
Aircraft maintenance operations are carried out by aircraft maintenance technicians (AMTs) with the necessary competencies and qualifications. The level of competency of maintenance technicians directly affects the safety and effectiveness of maintenance operations and flight operations. The aim of this study is to determine the safety culture and responsibility competencies and assessment methods for AMTs. Data related to the study were collected by conducting individual interviews and focus group discussions with 83 participants. The data were analyzed using the content analysis method and coding technique. As a result of individual interviews and focus group discussions with the participants, it was decided to use “safety perception (30.14%)” “aviation culture (29.58%)” “personal protective equipment (PPE) (28.73%)” “risk perception (6.48%)” and “occupational health and safety (5.07%)” to assess safety culture competency. It was decided to use “attendance (40.08%)” “work ethics (25.95%)” “reporting and suggestion (18.99%)” and “health and wellness (14.98%)” to assess responsibility competency. It has been determined that individuals such as technicians with relevant competencies, human factors specialists, and aviation psychology specialists should take part as assessors, as well as safety management system (SMS), quality, and human resources units in the assessment processes of the competencies.